Information and Communication Technology (ICT) as intermediary for knowledge reusability in knowledge management / Muhamad Khairulnizam Zaini, Mohd. Sazili Sahibi and Juwahir Ali - Zaini, Muhamad Khairulnizam; Sahibi, Mohd. Sazili; Ali, Juwahir (Faculty of Information Management, 2010)
Advances in information and communication technology (ICT) has inspired organizations of various functions to deploy diverse types of Internet and Intranet technologies to enhance knowledge coordination and sharing within organizations using of variety of technological tools. In fact, one of the key themes in knowledge management (KM) today's is the role of ICT in the transfer of knowledge between those who have it and those who do not. Presently KM involves the awareness of the importance of the retrieve-ability and also the arrangement description and structure of that content to be represented in the repository for the process of sharing and reusability. This has raised the concern of integration with the technology that can be used to support KM. Technology is an important facilitator and can help in overcoming the problems of KM. Information technology is considered to have a central role in organizing knowledge, both in order to enable sharing and collaboration or more explicitly through defining, storing and categorizing different knowledge units, which later on can be retrieved and presented as meaningful information across contexts. The purpose of this article is to investigate from literatures and researches the roles of ICT technical intermediary to support knowledge reusability process in organization